Remote sensing education at university of technology Malaysia for supporting local related industries in attaining sustainable natural resource and environmental managements - Hashim, Mazlan; Ibrahim, Ab. Latif; Mohd. Ibrahim, Seeni Mohd.; Ahmad, Samsudin (2004)

(untitled)
Since the beginning of the remote sensing development, remarkable progress has been made in utilizing remote sensing data, to describe, study, monitor and model the earth's surface and interior. Remote sensing is rapidly becoming accepted as an excellent tool for decision- making process. The present trend of development in remote sensing is focused on the improvements in the sensor technology, especially in the spatial, spectral, and radiometric resolution. These improvements have enabled the scientific community to operationalise the methodology as well as broadening applications of remote sensing data in particular to support sustainable natural resource and environmental managements. The main objective of this paper is to highlight the remote sensing education programmes offered at the University of Technology Malaysia both at undergraduate and postgraduate levels. This programmes is very important as a measure to fulfilled human resource requirements to support the related industries in utilization of the technology for attaining sustainable natural resource and environmental management in Malaysia. The curriculum for the courses, facilities and related research works that have been carried out are also highlighted.